Application of the CATA methodology with children: Qualitative approach on ballot development and product characterization of innovative products. (March 2021) - Rocha, Célia; Ribeiro, José Carlos; Costa Lima, Rui; Prista, Catarina; Raymundo, Anabela; Vaz Patto, Maria Carlota; Cunha, Luís Miguel
Abstract: There is an increasing importance of the role of children and adolescents in the food market and to successfully develop food products intended for them, it is necessary to apply proper sensory evaluation methodologies. Although children can execute traditional methods for food liking and preference evaluation, traditional sensory descriptive methods may not be suitable for them and it is necessary to assess their ability to perform novel sensory profiling methods. Thus, this study aimed to assess children's acceptance of an innovative food product – cookies incorporating fermented grass pea ( Lathyrus sativus ) flour – and their ability to describe a sensory profile using a Check-All-That-Apply (CATA) approach. Two different types of cookies (salty and sweet) were developed, differing in the level of substitution of wheat flour by fermented grass pea flour (between 0 and 40%). The cookies were evaluated by two sensory panels of 60 children (8–12 years), who assessed the overall liking using a 7-point facial hedonic scale and the sensory profile of the samples using a CATA ballot with 21 sensory terms previously developed through focus groups with children. Children showed the ability to discriminate the different samples with the hedonic scale and according to their sensory profile. Results revealed that the focus-group with children is an adequate way to generate CATA ballots and that the CATA approach is adequate to evaluate how children discriminate the sensory profile of food products. Furthermore, the food neophobia level of the children negatively impacted their acceptance of the food products.